Kecukupan Nutrisi pada Pasien Kanker - Hariani, Ririn (Indonesian Journal of Cancer, 2007)
Malnutrition is a common problem in cancer patients. Cancer cachexia refers to a complex multifactorial syndrome characterized by anorexia or the spontaneous and unintended loss of appetite, generalized host tissue wasting, skeletal muscle atrophy, immune dysfunction and a variety of metabolic alteration. The malnourished cancer patients respond poorly to therapheutic intervention. Once the patients have been screened and assessed, a nutrition care plan can be developed that is tailored to the patients present status, nutritional status, nutritional need, dietary restriction, tolerance and feasibility gastrointestinal function and treatment modalities that might impact their nutritional status, thus compromising intake. The calory requirements of patients with cancer depend on degree of malnutrition and metabolic stress, but also on calory losser and the level of physical activity. The aim of nutritional support should be the prevention or reversal of malnutrition, and this should be initiated early as possible to improve outcomes.Key Word: cancer patients, calory requirement, nutritional support